2005
DOI: 10.1128/jcm.43.4.1776-1781.2005
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing versus Pulsed-Field Gel Electrophoresis for Characterization of Extended-Spectrum Beta-Lactamase-Producing Escherichia coli Isolates

Abstract: Extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli strains are emerging pathogens. Molecular typing of ESBL-producing E. coli is useful for surveillance purposes, to monitor outbreaks and track nosocomial spread. Although pulsed-field gel electrophoresis (PFGE) is the current "gold standard" for bacterial molecular typing, multilocus sequence typing (MLST) may offer advantages. Forty ESBL-producing E. coli isolates were selected at random from a cohort of intensive care unit patients who had ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
2
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 29 publications
3
49
2
3
Order By: Relevance
“…A similar observation was made by Noller et al, who compared PFGE and MLST for their discriminatory ability using a collection of diarrheagenic E. coli serotype O157:H7 (16). In one study, MLST was found to be more discriminatory than PFGE only if gene templates in addition to the 7 housekeeping genes were included (15).…”
Section: Discussionmentioning
confidence: 65%
“…A similar observation was made by Noller et al, who compared PFGE and MLST for their discriminatory ability using a collection of diarrheagenic E. coli serotype O157:H7 (16). In one study, MLST was found to be more discriminatory than PFGE only if gene templates in addition to the 7 housekeeping genes were included (15).…”
Section: Discussionmentioning
confidence: 65%
“…Increasing antimicrobial resistance (42) and the ability of A. baumannii to survive on inanimate and dry surfaces (19) have been linked to the occurrence of outbreaks observed in various hospitals (5). MLST has emerged as the technique of choice for studying the population structure of many bacterial species (15,17,20,30,40), including A. baumannii (1,10,24,29,37,38). However, profiles for only 93 isolates of A. baumannii are available in the current MLST database (http://pubmlst.org/abaumannii/), which is considerably less than the numbers deposited in databases for other bacteria (http://pubmlst.org/databases.shtml).…”
Section: Vol 48 2010 Characterization Of Unrelated a Baumannii Isomentioning
confidence: 95%
“…MLST schemes for Enterobacteriaceae (27,28) and thus is appropriate for evolutionary population genetics. Additionally, wholegenome comparison of the eight publicly available K. oxytoca genome sequences was done using genomic BLAST, followed by dendrogram construction based on genetic distance.…”
Section: Discussionmentioning
confidence: 99%